Odpowiedź:
a)
f(x) = [tex]3x^{2}[/tex]- 2x
f(-2) = 3 * [tex]2^{2}[/tex] - 2 * (-2)
f(-2) = 3 * 4 - (-4)
f(-2) = 12 + 4
f(-2) = 16
b)
g(x) =-[tex]\frac{2}{3} x[/tex]+5
g(1) =-[tex]\frac{2}{3}[/tex] * 1+5
g(1) =-[tex]\frac{2}{3}[/tex] +5
g(1) =-[tex]\frac{2}{3}[/tex] +[tex]\frac{5}{1}[/tex]
g(1) =-[tex]\frac{2}{3}[/tex] +[tex]\frac{15}{3}[/tex]
g(1) = -[tex]\frac{13}{3}[/tex]
g(1) = -4 [tex]\frac{1}{3}[/tex]
c)
h(x) =2 [tex]\sqrt{3x}[/tex]- 8[tex]\sqrt{3x}[/tex]
h(-3) = 2[tex]\sqrt{3 * (-3)}[/tex] - 8[tex]\sqrt{3 * (-3)}[/tex]
h(-3) = 2[tex]\sqrt{-9}[/tex] - 8 [tex]\sqrt{-9}[/tex]
h(-3) = -2[tex]\sqrt{9}[/tex] - (-8)[tex]\sqrt{9}[/tex]
h(-3) = -2[tex]\sqrt{9}[/tex] +8[tex]\sqrt{9}[/tex]
h(-3) = 6[tex]\sqrt{9}[/tex]